The geology, geochemistry and silicate mineralogy of the upper criticial zone of the north-western Bushveld Complex, at Rustenburg Platinum Mines, Union Section - De Klerk, William Johan (Rhodes University, Faculty of Science, Department of Geology, 1982)
Rustenburg Platinum Mines, Union Section, is located in the mafic phase of the north-western sector of the Bushveld Complex. This part of the Complex is characterised by transgressions of Upper zone ferrogabbros across the lower sequence of mafic rocks. These transgressions have effectively isolated a roughly triangular segment of Lower, Critical and Main zone rocks. It is in the upper part of the Critical zone that the Merensky Reef, with a strike length of 9,5 km, is found to suboutcrop below a 2-3 m black turf soil cover and it constitutes the orebody being mined at Union Section. Underground mining and development have exposed a stratigraphic succession from the Middle Group chromitites to within the lower part of the Main zone gabbros. A detailed investigation of a 100 m stratigraphic succession was undertaken in the upper part of the Critical zone, which includes the Bastard Reef, Merensky Reef, Pseudo Reef, UG 2 and UG 1 layers. Stratigraphic descriptions are presented for both a normal and potholed succession, as well as a description of pothole characteristics. The variations of Merensky Reef thickness, pothole distribution and structure of the are body are also discussed. Forty seven whole-rock major- and trace-element analyses were carried out on selected samples from both normal and potholed successions, although more emphasis was placed on the former. These samples were taken from just below the UG 1 to above the Bastard Reef. Trace elements determined included Sr, Rb, Y, Nb, Zr, Cr, Co, Ni, Cu and V. The cyclical nature of the layering is clearly defined by breaks in the trends of both the major- and trace element analyses, although some elements are strongly influenced by the modal proportions of the mai n mineral phases. Although major breaks are observed for individual elements , insignificant variation of the Mg/Mg+Fe 2 + ratio is observed throughout. New electron microprobe data are presented for the main silicate phases olivine , orthopyroxene, clinopyroxene and plagioclase , while only a limi ted number of analyses were carried out on the spine l phase. There would appear to be a reversal of the expected fractionation trend from the hanging wal l of the UG 2 to the Pseudo Marker layer. There is an upward increase of the Fo content of the olivine from F0â‚‡â‚† , â‚‡â‚‹â‚ˆâ‚ ,â‚† . A similar trend is observed for the orthopyroxene analyses . The Merensky unit, as a whole, exhibits a gradual decrease in the Mg end member of the Ca-poor pyroxenes from En â‚‡â‚ˆ,â‚…â‚‹â‚‡â‚„ . was found to be markedly more calcic Cumulus plagioclase (An â‚‡â‚‚, â‚ˆ-â‚ˆâ‚ , â‚‡) than the intercumulus phase (Anâ‚…â‚†,â‚ƒâ‚‹â‚‡â‚ , â‚‰) ' A further feature of the cumulus plagioclase is that strong zonation was observed with the cores of individual crystals being consistently lower in Ca relative to their margins .,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Mineralogy -- South Africa -- North-Western Transvaal; Geochemistry -- South Africa -- North-Western Transvaal; Geology -- South Africa -- North-Western Transvaal; Platinum mines and mining -- South Africa -- North-Western Transvaal; Rustenburg Platinum Mines